Impact of rising seawater temperature on a phagocytic cell population during V. parahaemolyticus infection in the sea anemone E. pallida - Billaud, Mélanie; Larbret, Frédéric; Czerucka, Dorota (Frontiers in Immunology, 2023)
Climate change is increasing ocean temperatures and consequently impacts marine life (e.g bacterial communities). In this context, studying host-pathogen interactions in marine organisms is becoming increasingly important, not only for ecological conservation, but also to reduce economic loss due to mass mortalities in cultured species. In this study, we used Exaiptasia pallida (E. pallida), an anemone, as an emerging marine model to better understand the effect of rising temperatures on the infection induced by the pathogenic marine bacterium Vibrio parahaemolyticus. The effect of temperature on E. pallida were examined at 6, 24, or 30 hrs after bath inoculation with 108 CFU of V. parahaemolyticus expressing GFP (Vp-GFP) at 27°C (husbandry temperature) or 31°C (heat stress). Morphological observations of E. pallida and their Hsps expression demonstrated heat stress induced increasing damage to anemones. The kinetics of the infections revealed that Vp-GFP were localised on the surface of the ectoderm and in the mucus during the first hours of infection and in the mesenteric filaments thereafter. To better identify the E. pallida cells targeted by Vp-GFP infection, we used spectral flow cytometry. E. pallida cell types were identified based on their autofluorescent properties. corresponding to different cell types (algae and cnidocytes). We identified an AF10 population whose autofluorescent spectrum was identical to that of human monocytes/macrophage, suggesting that this spectral print could be the hallmark of phagocytic cells called “amebocytes''. AF10 autofluorescent cells had a high capacity to phagocyte Vp-GFP, suggesting their possible role in fighting infection. This was confirmed by microscopy using sorted AF10 and GFP-positive cells (AF10+/GFP+). The number of AF10+/GFP+ cells were reduced at 31°C, demonstrating that increased temperature not only damages tissue but also affects the immune response of E. pallida. In conclusion, our study provides a springboard for more comprehensive studies of immune defence in marine organisms and paves the way for future studies of the dynamics, activation patterns, and functional responses of immune cells when encountering pathogens.